Heat-Wave Events in Spain: Air Mass Analysis and Impacts on 7Be Concentrations. (22nd June 2016) - Hernández-Ceballos, M. A.; Brattich, E.; Cinelli, G.
Abstract : The present paper describes and characterizes the air mass circulation during the heat-wave events registered during the period 2005–2014 over Spain, paying special attention to the role of the Saharan circulations. Backward trajectories at 500, 1500, and 3000 m in Seville (south), Madrid (centre), and Bilbao (north) during the thirteen heat-wave events identified are analysed. Finally, the impact of the heat-wave events and of each advection pattern on 7 Be activity concentrations is also analysed. The heat-wave events are characterized roughly by western, southern, and nearby advections, with a higher frequency of the first two types. The analysis shows an increase of African air masses with height, presenting a different spatial impact over Spain, with a decreasing occurrence and a decrease in the simultaneous occurrence percentage from south to north. On average, the 7 Be activity concentrations during these events show an increase of concentrations in central (21%) and southern (18%) areas and a decrease in northern (13%) Spain. This increase is not associated with Saharan air masses but instead with the arrival of distant westerly air masses.